Trichomonas Vaginalis Infection Among Students of University of Port Harcourt - N., Eze Chinwe; Okwuchi, Edwin Queen (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2020)
Trichomonas vaginalis is one of the most common curable sexually transmitted disease. Untreated Trichomoniasis in women can cause cervicitis, vaginites and pelvic inflammatory disease. Trichomonas vaginalisis contributes to high risk of cervical cancer in women and HIV in men. This is an institutional based cross- sectional descriptive study conducted among two hundred (200) female students of Delta Hostels, University of Port Harcourt. High vaginal swabs (HVS) and urine samples were collected from consented students and examined for the presence of T. vaginalis under the microscope. A total of 32(16%) were infected and results obtained from HVS showed a prevalence of 32% compared to urine microscopy which no positive sample was detected. Students between the age group 15-25yrs had the highest prevalence of infection 31(17.2%) while the age group 26-35 years had 1(5%). However, the difference was statistically significant. Based on marital status all were single and had 32(16%) prevalence. This study observed a high prevalence of T. Vaginalis and its symptoms among the study population. The study also noted that high vaginal swab microscopy showed better detection sensitivity compared to urine microscopy. The best option for prevention and control is to educate students on personal hygiene and safe sex practice.